2016
DOI: 10.1016/j.ijmyco.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone consumption and -resistance trends in Mycobacterium tuberculosis and other respiratory pathogens: Ecological antibiotic pressure and consequences in Pakistan, 2009–2015

Abstract: We discuss the possible reasons for the decrease in resistance rates in TB, putative drivers of resistance other than volume of FQ consumption, and the possible impact of the National Tuberculosis Programme and drug regulatory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Instead, as shown by comparison between two subgroups of patients treated for over 6 months, fluoroquinolone use can slightly increase the prevalence of fluoroquinolone resistance. A similar weak relationship between fluoroquinolone resistance and fluoroquinolone consumption for M. tuberculosis has been demonstrated previously [15].…”
Section: @Erspublicationssupporting
confidence: 85%
“…Instead, as shown by comparison between two subgroups of patients treated for over 6 months, fluoroquinolone use can slightly increase the prevalence of fluoroquinolone resistance. A similar weak relationship between fluoroquinolone resistance and fluoroquinolone consumption for M. tuberculosis has been demonstrated previously [15].…”
Section: @Erspublicationssupporting
confidence: 85%
“…12,13 Many other studies from different regions have also demonstrated weak relationship between prior FQ use and FQ resistance. [14][15][16] The correlation between resistance to a drug (other than rifampicin and isoniazid) and prior intake of the same drug was not found to be statistically significant for any drug. According to a study by Hamusse et al, individuals with previous history of TB treatment were eight times more likely to develop resistance to any first-line anti-TB drugs compared to those with no history of previous TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sparfloxacin has shown an efficient and safe alternative in treating complex TB and is the only appropriate substitute drug at present to treat some cases of MDR‐TB. [ 50 ] Sokolova et al, have studied the efficiency and safety of sparfloxacin in combination therapy for drug‐susceptible and drug‐resistant pulmonary TB through enrolling 60 members with severe pulmonary‐TB. Sparfloxacin was combined with other anti‐TB drugs to create highly effective combinations.…”
Section: Advances In Preclinical Developmentmentioning
confidence: 99%